อัตราผลตอบแทนจากการลงทุนทางการศึกษาวิทยาลัยเอกชน กรณีศึกษา: คณะพยาบาลศาสตร์ (RATE OF RETURN ON PRIVATE COLLEGE: CASE STUDY OF FACULTY OF NURSING) - ชัยทัศน์, จักรพันธ์; มนัสสนิท, วัชรี; สุวรรณจินดา, เฌณิศา (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2018)
The objective of this research were to study rate of return on private college case study of faculty of nursing chiangrai college. This study consist of 1) The direct and indirect private cost of graduates per head 2) The estimated of graduates income and 3) An analysis rate of return on investment in education. The populations for study is the graduates from nursing faculty, Chiangrai College. The results of the study found that 1) The graduates total private cost per head was 1,023,324.736 baht which consist of the direct and indirect private costs were 600,000 and 423.324.736 baht. 2) an estimated from graduates income found that the higher work experiences graduates has higher income than the lower work experiences graduates. Those who worked in private sector earned higher income than those who worked in government sector and 3) an analysis rate of return found that benefit-cost ratio for total graduates was 266.86, for those who worked in the private sector was 342.08 while of those who worked in government sector was 222.84. Internal rate of return total graduates was 28.84%, for those who worked in private sector was 31.97% while of those who worked in government sector was 26.76%.